Experimental Progress on Quantum Coherence: Detection, Quantification, and Manipulation. Issue 9 (13th July 2021) - Wu, Kang‐Da; Streltsov, Alexander; Regula, Bartosz; Xiang, Guo‐Yong; Li, Chuan‐Feng; Guo, Guang‐Can
Abstract: Quantum coherence is a fundamental property of quantum systems, separating quantum from classical physics. Recently, there has been significant interest in the characterization of quantum coherence as a resource, investigating how coherence can be extracted and used for quantum technological applications. In this work, the progress of this research is reviewed, focusing in particular on recent experimental efforts. After a brief review of the underlying theory, the main platforms for realizing the experiments are discussed: linear optics, nuclear magnetic resonance, and superconducting systems. Experimental detection and quantification of coherence, experimental state conversion and coherence distillation, and experiments investigating the dynamics of quantum coherence are then considered. Experiments exploring the connections between coherence and uncertainty relations, path information, and coherence of operations and measurements are also reviewed. Experimental efforts on multipartite and multilevel coherence are also discussed. Abstract : The resource theory of quantum coherence has been extensively studied in a variety of different contexts and applications. Focusing on the experimental progress in this field, the authors give a comprehensive overview of the various aspects of coherence as a resource and its practical investigation.